(3eUGOQ GdEdJRGe (B:s (3GdaYd GdVGQ hGdaYd GdfGaY, GdbGfhf (B/s - (3efUhQ, eMeO MSjfs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3GdbGfhf ceUOQ ddEdJRGe(B-(3eaghe GdeSDhdjI GdJbUjQjI(B-(3GdeSDhdjI Yf GdCYeGd GdTNUjI(B((3GdJHYI GdfGLeI Yf GdaYd GdTNUj(B)-(3GdeSDhdjI Yf aYd GdZjQ(B-(3GdeSDhdjI Yf GdCTjGA(B-(3JYhjV GdVQQ(B-(3eHOC GdEKQGA HdG SHH(B-(3OaY ZjQ GdeSJMb(B((3EjaGA eG dG jLH(B)-(3GdaVGdI(B((3GdaVhd(B)s
Keywords: (3GdEdJReGJs; (3GdbGfhfs